2010
DOI: 10.1097/mlr.0b013e3181e57962
|View full text |Cite
|
Sign up to set email alerts
|

US Pharmacists' Effect as Team Members on Patient Care

Abstract: Pharmacist-provided direct patient care has favorable effects across various patient outcomes, health care settings, and disease states. Incorporating pharmacists as health care team members in direct patient care is a viable solution to help improve US health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
550
3
19

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 692 publications
(588 citation statements)
references
References 28 publications
16
550
3
19
Order By: Relevance
“…In addition, the issue of cost-related nonadherence is not routinely addressed during patient encounters. 4,[7][8][9][10][11][12][13][14][15] This study demonstrated that a single lecture given by pharmacy students to other health care professional students and current prescribers can improve knowledge of prescription drug cost-containment strategies targeting vulnerable patient populations and can increase the likelihood of collaboration between prescribers and pharmacists. While future studies should determine if this intervention changes clinical practice and reduces patients' actual OOP prescription drug costs, these results show that this lecture format is an efficient way to disseminate important and timely information to health care professionals as they begin to practice in the new health care delivery models outlined in health care reform.…”
Section: ■■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the issue of cost-related nonadherence is not routinely addressed during patient encounters. 4,[7][8][9][10][11][12][13][14][15] This study demonstrated that a single lecture given by pharmacy students to other health care professional students and current prescribers can improve knowledge of prescription drug cost-containment strategies targeting vulnerable patient populations and can increase the likelihood of collaboration between prescribers and pharmacists. While future studies should determine if this intervention changes clinical practice and reduces patients' actual OOP prescription drug costs, these results show that this lecture format is an efficient way to disseminate important and timely information to health care professionals as they begin to practice in the new health care delivery models outlined in health care reform.…”
Section: ■■ Conclusionmentioning
confidence: 99%
“…As experts in prescription drug selection, use, and cost, pharmacists are in a unique position to help manage patients' prescription drug therapy to achieve maximal therapeutic benefit while keeping patients' OOP prescription drug costs low. 11 Prior research has shown that Medicare Part D lectures delivered by trained pharmacy students led to a statistically • Passage of the Affordable Care Act in 2010 has put an increased focus on the need for health policy education in health professional schools. This lecture provides a timely and efficient method of communicating health policy information between professionals.…”
Section: Setting Intervention and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A technical package of a limited number of highpriority, evidence-based interventions that together will have a major impact: Positive clinical evidence of medication therapy management (MTM) with respect to Patient-Centered Medical Home (PCMH) and Employer-based Pharmacist/Ambulist (EBPA) have been demonstrated and supports pharmacists in various interprofessional and collaborative team-based care roles. 26,27 Significant improvements in therapeutic and safety outcomes, such as hemoglobin A1c, LDL cholesterol, blood pressure, and adverse drug events, further supports the effectiveness of pharmacist in team-based patient care. 28 Thus, the technical package involves specific activities related to MTM delivered thorough PCMH and EBPA.…”
Section: Wellness and Preventionmentioning
confidence: 99%
“…Several studies have shown that the insertion of the pharmacist in the multidisciplinary team results in more cost-effective outcomes, but most of these studies were directed to the study of specific public, disease or situation [1][2][3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%